Strengthening international negotiation assistance for developing host countries - Vanessa Tsang (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2022)
It is important for developing host countries to ensure that the investment contracts they enter into with foreign investors are fit-for-purpose and effectively protect the parties' often competing commercial interests. To ensure that these contracts are fair and equitable, host countries may need to rely on international negotiation support.
Keywords: 330